2020
DOI: 10.18203/2349-3933.ijam20203603
|View full text |Cite
|
Sign up to set email alerts
|

A study of magnitude and correlates of altered bone mineral density in type 2 diabetes mellitus patients of central rural India

Abstract: Background: Diabetes mellitus is fast becoming the epidemic of the 21st century. It is a metabolic disease that affects multiple organ system in the body including bone metabolism and bone mass. There is high prevalence of decreased bone mineral density (BMD) in type 2 diabetes mellitus (T2DM) patients leading to osteoporosis, osteopenia and fracture. The aim of the present study was to find the magnitude and correlates of altered BMD in T2DM patients of central rural India.Methods: This cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Though Prakash et al [10] also reported the prevalence of osteopenia and osteoporosis to be quite high (69.8%), however, in their study the prevalence of osteoporosis was higher (43.8%) as compared to osteopenia (26%). Reema et al 11 reported the overall prevalence of osteopenia and osteoporosis to be close to our study (82% vs 86% in our study), yet in their study proportion of osteoporosis was much higher (53%) than our study (39%) whereas proportion of those with osteopenia was much lower (29%) than our study (47%). These finding suggest that although, there is a high prevalence of osteopenia and osteoporosis in T2DM patients yet the pattern and spectrum of these BMD abnormalities shows a considerable variance.…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…Though Prakash et al [10] also reported the prevalence of osteopenia and osteoporosis to be quite high (69.8%), however, in their study the prevalence of osteoporosis was higher (43.8%) as compared to osteopenia (26%). Reema et al 11 reported the overall prevalence of osteopenia and osteoporosis to be close to our study (82% vs 86% in our study), yet in their study proportion of osteoporosis was much higher (53%) than our study (39%) whereas proportion of those with osteopenia was much lower (29%) than our study (47%). These finding suggest that although, there is a high prevalence of osteopenia and osteoporosis in T2DM patients yet the pattern and spectrum of these BMD abnormalities shows a considerable variance.…”
Section: Resultssupporting
confidence: 52%
“…Similar to our observations, Sharma et al [6] also found BMD to be lower in females as compared to males. Studies by other workers also supported this observation [10,11].…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations